2023
DOI: 10.1007/s40123-023-00658-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Central Serous Chorioretinopathy in Male Androgen Abusers

Abstract: Introduction: Male gender is an important risk factor of central serous chorioretinopathy (CSC), and studies have explored the pathophysiological role of androgens in CSC with conflicting results. In this study, we shed light on this hot topic by exploring the risk of CSC in a large cohort of male androgen abusers. Methods: This study included male androgen abusers identified through a nationwide antidoping test program across Danish fitness centers from January 3 2006 to March 1 2018. For each case, we random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Tis was due to the strict exclusion of any patient with signs of CNV or PCV in our patient screening. Tis also led to a younger age of the included patients, especially female patients, which was associated with a greater incidence of CNV (38,39). In addition, another noteworthy point was the smaller male/female ratio (2.2/1) in our study population.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Tis was due to the strict exclusion of any patient with signs of CNV or PCV in our patient screening. Tis also led to a younger age of the included patients, especially female patients, which was associated with a greater incidence of CNV (38,39). In addition, another noteworthy point was the smaller male/female ratio (2.2/1) in our study population.…”
Section: Discussionmentioning
confidence: 80%
“…However, Subhi et al explored the risk of CSC in a large cohort of male androgen abusers in a recent study. These authors speculated that androgen plays a subtle role at best in the pathophysiology of CSC [ 39 ]. Thus, we speculated that the potentially different effects on males and females caused by the weak estrogen-like effects of spironolactone might be relatively weak and had little function in therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 47 This sex-dependence to androgen exposure disappeared upon overexpression of AR in the female derived ECs. Therefore, even if CSC development is not directly related to androgen levels, 19 , 48 unresponsiveness to any circulating androgens in young women could potentially explain that CSC occurs more in young men.…”
Section: Discussionmentioning
confidence: 99%
“…Central serous chorioretinopathy (CSC) is the fourth most common maculopathy and an exudative maculopathy that primarily presents in males aged 30–50 years (Kido et al, 2022; van Rijssen et al, 2019). Studies have identified endogenous or exogenous corticosteroids as important risk factors, but their exact aetiological role remains incompletely understood (Brinks, van Dijk, Kiełbasa, et al, 2022; Holtz et al, 2022; Subhi et al, 2023). Imaging studies find that venous outflow obstruction and arteriovenous anastomoses lead to a pachychoroid phenomenon of enlarged congested choroidal vessels (Brinks, van Dijk, Meijer, et al, 2022; Cheung et al, 2019; Spaide et al, 2022).…”
Section: Introductionmentioning
confidence: 99%